NONCONVENTIONAL POWER TOOLS: REAL-TIME THERMAL EXPANSION MONITORING FOR BRUSHLESS MOTORS (Nonconventional Technologies Review, 2023)
The power tools industry has been propelled into a new era of innovation through the widespread integration of brushless motors. These sophisticated powerhouses have revolutionized the industry by delivering heightened efficiency, prolonged operational lifespans, and elevated power output, fundamentally reshaping the standards of performance. Despite these remarkable advantages, the journey toward excellence is not without its challenges. A central predicament lies in the intensified heat generation intrinsic to brushless motors, culminating in a complex phenomenon known as thermal expansion. This article embarks on an intricate exploration, shedding light on the transformative potential of real-time thermal expansion monitoring as a pivotal solution within the realm of brushless motors.
Keywords: brushless motors; power tools; thermal expansion; real-time monitoring; performance enhancement